Sleeptalking! Sleepwalking! Side Effects of Montelukast - Samer Alkhuja; Natalya Gazizov; Mary Ellen Alexander (Case Reports in Pulmonology)
A 16-year-old Caucasian female presented to the pulmonary clinic for a followup on her asthma. Due to the worsening of allergy-related symptoms, therapy with montelukast 10 mg daily was started and resulted in good relief of the patient’s symptoms. In the nights following initiating therapy with montelukast, the patient’s mother reported daily parasomnias in the form of sleeptalking and sleepwalking. Montelukast was discontinued, and that resulted in absence of the parasomnias. In a second attempt montelukast was reinstituted to control the patient’s symptoms. Parasomnias were immediately reported after resuming therapy. Montelukast was then discontinued indefinitely. Our patient has never had any history of parasomnias, and since the discontinuation of montelukast, parasomnias were never reported again. Parasomnias in the form of sleeptalking or sleepwalking were not previously reported as adverse effects of montelukast. Alternative modalities to treat allergy-related symptoms in patients, who develop parasomnias while receiving montelukast, should be explored.